Care, migration, and human rights : law and practice - Mullally, Siobhan (Milton Park, Abingdon, Oxon, : Routledge, 2015)
'This book addresses the specific position of domestic workers in the context of evolving human rights norms. Human rights law has somewhat belatedly begun to address the structured inequalities and exclusions that define the domain of domestic work. The continuum of exploitation that has historically defined the everyday of domestic work exclusion from employment and social security standards and precarious migration status have frequently been neglected. However, as in other areas of international law, it is primarily the moments of crisis, incidents of human trafficking, slavery or forced labour, that have captured the attention of human rights law. Drawing upon a broad range of case studies, Care, Migration and Human Rights presents a thorough examination of key issues such as the commodification of care, the impact of the jurisprudence of the CJEU and the European Court of Human Rights on'primary care providers', as well as the effect that trends in migration law have on migrant domestic workers. In addition to the question of how migration status impacts upon the effective realisation of rights, the editors also explore wider problems such as the continuing gendered division of labour and the absence of state or societal supports. This volume will be of interest to lawyers, academics and policy makers in the fields of human rights, migration, and gender studies'--
'This book addresses the specific position of domestic workers in the context of evolving human rights norms. Human rights law has somewhat belatedly begun to address the structured inequalities and exclusions that define the domain of domestic work. The continuum of exploitation that has historically defined the everyday of domestic work exclusion from employment and social security standards and precarious migration status have frequently been neglected. However, as in other areas of international law, it is primarily the moments of crisis, incidents of human trafficking, slavery or forced labour, that have captured the attention of human rights law. Drawing upon a broad range of case studies, care, migration and human rights presents a thorough examination of key issues such as the commodification of care, the impact of the jurisprudence of the CJEU, and the European Court of Human Rights on'primary care providers', as well as the effect that trends in migration law have on migrant domestic workers. In addition to the question of how migration status impacts upon the effective realisation of rights, the editors also explore wider problems such as the continuing gendered division of labour and the absence of state or societal supports. This volume will be of interest to lawyers, academics, and policy makers in the fields of human rights, migration, and gender studies'--
Introduction : decent work, domestic work : gendered borders and limits / Siobhan Mullally -- Care of work? The tyranny of categories / Ann Stewart -- Care work in the European court of human rights' case law : beyond servitude and forrced labour? / Fulvia Staiano -- Migrant domestic workers in the UK : enacting exclusions, exemptions and rights / Siobhan Mullally and Cliodhna Murphy -- Obstacles to claiming rights : migrant domestic workers in Asia's world city, Hong Kong / Nicole Constable -- Access to justice for undocumented migrant domestic workers in Europe : the consequences of constructed illegality / Cliodhna Murphy -- Traditions, law and practice : migrant domestic workers in Lebanon / Gulnara Shaninian -- Migrant Filipino domestic workers in Pakistan : agency, rights and the limits of the law / Ayesha Shahid.
Includes bibliographical references and index.
Keywords: Household employees -- Legal status, laws, etc; Migrant labor -- Legal status, laws, etc; Household employees -- Abuse of; Migrant labor -- Abuse of; Human rights